Intorno a Boccaccio / Boccaccio e dintorni 2020 Atti del Seminario internazionale di studi (Certaldo Alta, Casa di Giovanni Boccaccio, 10-11 settembre 2020) - Frosini, Giovanna (Studi e saggi, 2021)
Intorno a Boccaccio/Boccaccio e dintorni 2020 collects the Proceedings of the Seminar that took place in Certaldo Alta on 10-11 September 2020, in one of the short intervals that the pandemic has left open to face-to-face meetings. The Seminar, now in its seventh edition, is configured not only as one of the main activities of the Ente Giovanni Boccaccio, but as an international event, whose importance is confirmed by the continuous increase in citations in the scientific bibliography. The 2020 edition also qualifies for the relief and variety of the topics covered, for the merging and intertwining of historical-literary, philological, linguistic skills, which lead to reflect on important topics of Boccaccio's culture and sources and on his works, not without forgetting, in this centenary year 2021, the vital and fundamental relationship with Dante.